From safety nets to springboard: architecting a social and economic security system for an inclusive future - Raghavendra Suhasaa, H. G.; Shubha, B. N. (The International tax journal, 2025)
This report provides a comprehensive analysis of social enablement in India, examining its constitutional foundations, economic debates, and practical implementation through national and state-level welfare schemes. It evaluates their socio-economic impact, fiscal sustainability, and role within the political economy, navigating the contentious “freebies” versus welfare debate with a clear analytical framework. The analysis reveals a complex landscape of significance in poverty reduction, improved health and social indicators juxtaposed with persistent challenges of fiscal strain and implementation gaps. The report concludes by offering a strategic roadmap to transform India's fragmented welfare architecture into an integrated, resilient, and empowering system, capable of supporting the nation's ambition to become a developed economy by 2047 with inclusivity and sustainable prosperity.